Debates on Religious Studies In the Phenomenology Perspective and Its Contribution to Interfaith Tolerance - Akhiyat Akhiyat (Universitas Islam Negeri Mataram, 2019)
The phenomenological approach in religious studies has played an essential role in uncovering the mysteries of religious experience. With the epoché concept, which refers to the meaning of